Social-historical processes of writing practices in Ashánjnka communities - Alonzo Sutta, Alicia (2011)
According to the indigenous population of the Peruvian Amazon, the 20th century constituded a period of great changes. Jn the first decades, important events took place during the rubber period; in the following decades, and as a consequence of the previous events, the indigenous populations began to migrate and have contact with foreign populations. Halfway into the last century, the ashaninka population from High Perene (Chanchamayo-Junin) went through several changes, such as social, economic, and linguistic. Linguisticly, there was competition between Ashaninka-Spanish bilinguism and Ashaninka monolinguism. Jn the 70s and with the beginning of native communities (CCNN), schools were built, institutions of the official system of education, in which new methods were applied. Is in this context that written Spanish becomes a new activity assumed by the ashaninka population.